The Effectiveness of Coastal Environments Learning Media to Increase Elementary School Students' Cognitive Responses - Ribeh Najib Muhammad (Universitas Muhammadiyah Gresik, 2025)
Coastal environments have in recent years become the focus of government development with the hope of becoming a center for ecological protection and an educational tourism destination due to the large number of mangrove plant species and migratory bird species that stop by from various parts of the world. A high level of environmental awareness and good English language skills are very urgent to support the sustainability and benefits of this ecosystem and to expose it internationally. However, the majority of English language learning in schools focuses more on general knowledge without any specifications and differentiation tailored to the environment around students. Therefore, this research aims to determine the level of effectiveness of digital-based English learning media and the coastal environment with the hope of increasing elementary school students' cognitive response to the sustainability and optimization of coastal sustainability, which is located on the north coast of East Java. The research method used is mixed-method with explanatory sequential strategy conducted in three elementary schools located around the coastal area. Then the data obtained will be processed using nested ANOVA. The results of this research are crucial stages needed to create an effective integration model for English language learning and the environment that meets regional needs to accommodate the forthcoming policy from the ministry of education that will make English as one of the integral subjects in elementary school.